PERBEDAAN KEJADIAN INFEKSI CACING ANTARA PETUGAS PENGANGKUT SAMPAH YANG MENGGUNAAN ALAT PELINDUNG DIRI DENGAN PETUGAS PENGANGKUT SAMPAH YANG TIDAK MENGGUNAKAN ALAT PELINDUNG DIRI - Lezdyana Nur Islami; Sulastrianah Sulastrianah; Wa Ode Sitti Asfiah Udu (Halu Oleo University, 2014)
Soil Transmitted Helminth (STH) infection globally spread around the worlds. Incidence of helminth infection more common in childrens, but adult with special job like garbage workers have same risk with that childrens. The aim of this study is to determine differences between usage of personal protective equipment with the helminth infection among garbage workers that completely used personal protective equipement and that not completely used . The method of this study is an observational with cross sectional design. Population in this study are garbage workers at Sanitary Service Wakatobi Regency. Sampling method using total sampling with 59 samples. The data about usage of personal protective equipement have done by observation and faecal examination by direct slide. The differences analysed statistically using Chi-Square test. As a result, it is obtained that among the workers that not completely using personal protective equipment, there 27 (60%) samples are infected and 18 (40%) samples are not infected. Among the workers that completely using personal protective equipment, there is 4 (28,6%) samples are infected and 10 (71,4%) samples are not infected (p = 0,04). The conclusion of this study is there was relation between usage of personal protective equipment with helminth infection in garbage workers. Key Words: Helminth infection, garbage workers, personal protective equipment